Case report: Temporal alterations in vascular function during the first 2 weeks of pediatric septic shock - Wijers, Christiaan Diederik Mathijs; Stark, Ryan J. (Frontiers in Pediatrics, 2022)
Introduction: During sepsis and septic shock, the host’s immune systems generate an overwhelming and often, detrimental, inflammatory response. Part of this response results in significant alterations in blood flow and vasomotor tone regulated in part by endothelial and vascular smooth muscle cells. Here, we report on a series of 3 pediatric patients for whom vascular response was assessed by laser doppler perfusion coupled to iontophoresis over the first 2 weeks after hospitalization for septic shock to demonstrate similarities and dissimilarities in the vascular response. Case Presentations: A 12-year-old male with a history of Burkitt’s Lymphoma, a 21-year-old male with congenital porencephaly and epilepsy, and a 7-year-old male with no significant past medical history all were admitted to a tertiary care children’s hospital with a diagnosis of septic shock requiring vasoactive infusions to maintain mean arterial blood pressure. Non-invasive laser doppler perfusion coupled with iontophoresis of either acetylcholine (endothelial-dependent response) or sodium nitroprusside (endothelial-independent response) was performed on hospital days 1, 3, 7 and 14. Variability and heterogeneity were demonstrated by the temporal assessments of the vascular response to sodium nitroprusside, but all three patients showed significant similarity in the temporal responsiveness to acetylcholine. Conclusion: Assessment of baseline and temporal responsiveness to endothelial-dependent vascular reactivity may provide a predictable timeline to the resolution of pediatric septic shock.